Legal Remedies For Applicants For Land Registration Due To Inheritance That Has Been Distributed Inheritance But Rejected By The Land Office (Study In Blitar Regency) - Benneth Samuel Umbing; Iwan Permadi; Hariyanto Susilo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The inheritance is agreed to fall to one heir, then the registration of the transfer of rights to the land can be directly made to one heir who has been determined. However, the fact that the land registration that must be taken by the heirs is different from the rules listed in Article 42 paragraph (4) of PP No. 24 of 1997. The Land Office does not accept applications for registration of transfer of inheritance as stipulated in Article 42 paragraph (4) PP land registration, so that the registration of the land must be registered first to all heirs, after which a deed of Division of Joint rights (APHB) is made for the refusal, of course, there will be legal consequences for the applicant. The problem in this study is a legal remedy for applicants for land registration because of inheritance that has been the division of inheritance but rejected by the Land Office and how the legal protection for applicants for land registration because of inheritance that has been the division of inheritance but rejected by the Land Office. This type of research is normative legal research. The method of approach uses a legislative and conceptual approach. Data sources come from primary and secondary sources of law. The results of this study indicate that legal remedies for applicants for land registration due to inheritance that has been the division of inheritance but rejected by the Land Office the factors that affect the inadmissibility of the registration of the transfer of land rights due to inheritance based on APHW are ignorance of service counter employees about the rules of registration of the transfer of land rights due to inheritance based on APHW, namely Article 42 paragraph (4) of Government Regulation No. 24 of 1997 on Land Registration. There has been no direction from the superior to the Front Office related to the National Land Agency circular on instructions for registration of transfer of Rights due to inheritance, probate grants and distribution of rights with B/HR number.02/1012/IV / 2023 dated April 13, 2023. Alternative efforts that can be made by the parties so that the registration of the transfer of rights due to inheritance based on APHW can be applied, can be done by a notary/PPAT or from the applicant himself. Efforts that can be done by a notary/PPAT one of them by filing a complaint related Land Office.